Cardiovascular Health Effects of Internet-Based Encouragements to Do Daily Workplace Stair-Walks: Randomized Controlled Trial - Andersen, Lars Louis; Sundstrup, Emil; Boysen, Marianne; Jakobsen, Markus Due; Mortensen, Ole Steen; Persson, Roger (JMIR Publications, 2013)
BackgroundAlthough the hazardous health effects of a sedentary lifestyle are well known, many adults struggle with regular physical activity. Simple and efficient encouragements for increased physical activity are needed. ObjectiveTo determine the effect on cardiovascular health of email-based encouragements to do daily stair-walks at work together with colleagues among adults in sedentary occupations. MethodsA single-blind randomized controlled trial was performed at a large administrative company in Copenhagen, Denmark. Participants were 160 office workers (125 women, 35 men; mean age 42 years, SD 10; sitting 89.5% of work time). At baseline, aerobic fitness was 37 mL/min/kg (SD 9), mean blood pressure was 118/79 mmHg (SD 14/9), and mean body mass index (BMI) was 23 kg/m2 (SD 4). Participants were randomly assigned (2:1 ratio) to an email group receiving weekly email-based encouragements to walk the stairs for 10 minutes a day or to a control group receiving weekly reminders to continue their usual physical activities. The primary outcome was the change from baseline to 10-week follow-up in aerobic fitness determined from a maximal cycle test. The examiner was blinded to group allocation. ResultsAdherence to the email encouragements was fairly high with 82.7% of the participants performing at least 3 sessions of 10-minute stair-walks per week (mean 3.3, SD 1.3). Mean heart rate reached 167 beats/min (SD 10) during stair-walks. In the intention-to-treat analysis, aerobic fitness increased 1.45 mL/min/kg (95% CI 0.64-2.27) at 10-week follow-up in the email group compared with the control group. In participants with low aerobic fitness at baseline (n=56), aerobic fitness increased 1.89 mL/min/kg (95% CI 0.53-3.24), and systolic and diastolic blood pressure decreased 4.81 mmHg (95% CI 0.47-9.16) and 2.67 mmHg (95% CI 0.01-5.32), respectively, in the email group compared with the control group. Body weight decreased in the email group of those with low aerobic fitness compared with the control group, but this was not statistically significant. ConclusionsSimple and inexpensive email-based encouragements to do daily stair-walks together with colleagues at work improves cardiovascular health among adults in sedentary occupations. There exists an enormous potential to prevent the hazardous health effects of a sedentary lifestyle through the use of email-based encouragements to do short bouts of physical activity at the workplace. Trial RegistrationClinicaltrials.gov NCT01293253; http://clinicaltrials.gov/ct2/show/NCT01293253 (Archived by WebCite at http://www.webcitation.org/6HWG2jw68).